Enhanced extreme ultraviolet high-harmonic generation from chromium-doped magnesium oxide - Nefedova, V. E.; Fröhlich, S.; Navarrete, F.; Tancogne-Dejean, N.; Franz, D.; Hamdou, A.; Kaassamani, S.; Gauthier, D.; Nicolas, R.; Jargot, G.; Hanna, M.; Georges, P.; et al. (My University, 2021)
High-order harmonic generation (HHG) from crystals is emerging as a new ultrashort source of coherent extreme ultraviolet (XUV) light. Doping the crystal structure can offer a new way to control the source properties. Here, we present a study of HHG enhancement in the XUV spectral region from an ionic crystal, using dopant-induced vacancy defects, driven by a laser centered at a wavelength of 1.55 μm. Our numerical simulations based on solutions of the semiconductor Bloch equations and density-functional theory are supported by our experimental observations and demonstrate an increase in the XUV high harmonic yield from doped bulk magnesium oxide (MgO) compared to undoped MgO, even at a low defect concentration. The anisotropy of the harmonic emission as a function of the laser polarization shows that the pristine crystal's symmetry is preserved. Our study paves the way toward the control of HHG in solids with complex defects caused by transition-metal doping.